Exploring the effect of the indigenous technology of oil extraction on Grade 10 Biology learners' perspectives and sense making of enzymes - Nyamakuti, Martha Ndeyatila (Rhodes University, Faculty of Education, Department of Education)
The current status quo is that African learners' local indigenous knowledge (IK) and experiences from home (cultural heritage) are not considered in science classrooms. In the context of Namibia, it seems that the Namibian curriculum policies do little or nothing to decolonise and address the issues of equity and social injustice in Namibian schools. For instance, although the Namibian National Curriculum for Basic Education (NCBE) claims that it "embraces traditional knowledge" , it does not specify how this should be done in schools. As a result, little or no integration of IK is enacted in many of our schools in Namibia. Resultantly, learners seem to find science inaccessible and irrelevant to their everyday lives. It is against this background that in this study I sought to explore how the mobilisation of the indigenous technology of oil extraction (okuyenga) from marula nuts and melon seeds influences (or not) Grade 10 Biology learners' conceptions, dispositions and sense making of the topic of enzymes. The study was located within the interpretive and indigenous research paradigms. Central to the interpretive paradigm is the development of a greater understanding of how people make sense of the contexts in which they live and work. On the other hand, central to indigenous research paradigms are belief systems based on the lived experiences, values, and histories of the participants. The Ubuntu perspective or approach in which respect and humble togetherness is emphasised is critical in indigenous research paradigms especially when researchers are working with and in communities as I did in this study. The study was conducted in an under resourced school in Walvis Bay, Namibia. A qualitative case study approach was used and data were derived from a focus group interview, participatory classroom observations, learners' reflections, and a stimulated recall interview. Vygotsky's socio-cultural theory was employed as a theoretical framework. Within the socio-cultural theory, mediation of learning, social interactions, and the zone of proximal development (ZPD) were used as analytical lenses. The conceptual framework comprised of perspectives (conceptions, dispositions) and sense making of enzymes by the learners. Criteria were also adapted from Atallah, Bryant, and Dada to analyse learners' perspectives. A thematic approach to analysis was employed to come up with categories and sub-themes and thereafter, common sub-themes were combined to form themes. The findings of the study revealed that the presentations on the indigenous technology of oil extraction by the expert community members influenced learners' conceptions, dispositions, and sense making of enzymes and other associated science concepts. This was noticed when learners extracted emerging science concepts from the indigenous technology of oil extraction. The implication of this study is that there is a need for science teachers to consider learners' cultural heritage and integrate local IK in their Biology classrooms in order to make science accessible and relevant to learners. Moreover, the integration of local IK is critical for learners to embrace and respect their cultural heritage. This study thus recommends that teachers should make efforts to collaborate with expert community members who are the custodians of local IK and tap into their cultural heritage and wisdom to enrich teaching in their science classrooms.
Keywords: Biology-- Study and teaching (Secondary); Enzymes; Traditional ecological knowledge-- Namibia; Culturally relevant pedagogy-- Namibia; Reasoning; Contiguity Argumentation Theory (CAT); Namibian National Curriculum for Basic Education(NCBE); Socio-cultural theory